Chapter Seven: A Trade Facilitation Agreement Tool to Facilitate and Secure Trade - Toshevska trpchevska, Katerina; Kikerkova, Irena; Makrevska disoska, Elena (Cambridge Scholars Publishing, 2018)
The growing importance of trade facilitation is acknowledged with the signification of the new Agreement on Trade Facilitation at the WTO Ministerial Conference held in Bali in December 2013. The Trade Facilitation Agreement entered into force in February 2017 after two-thirds of the members completed their domestic ratification process. All countries agree that undertaking measures in this field can be beneficial for increasing their trade and the trade of their partners. The World Customs Organization has developed a methodology and software known as World Customs Organization Time Release Study (WCO TRS). WCO TRS is used to measure the time needed to release the goods and is a useful tool to identify weaknesses, risks and unsolved problems in cross border trade and international transport. Based on the negotiations that were conducted before the signing of the WTO Trade Facilitation Agreement, OECD undertook work to develop Trade Facilitation Indicators (TFIs) in order to measure their relative economic and trade impact on trade flows and trade costs in WTO member countries. In this chapter we are going to make an analysis and comparison of the results obtained from the methodology used by the World Customs Organization and the measures used by the OECD. The final goal of the chapter should be to sum up the results from both of the studies, find eventual similarities and offer recommendations that can be used by the official authorities either in Macedonia or within the region and wider to facilitate and secure trade.
Trade Perspectives in the Context of Safety, Security, Privacy and Loyalty
Keywords: Trade Facilitation Agreement; Time Release Study; OECD trade facilitation indicators; South-Eastern Europe